228k views
1 vote
Find the equation of a circle with a point at ( 10 , - 4 ) and a point at ( -2 , - 4 )​

User Shaul Dar
by
5.1k points

2 Answers

5 votes

Answer:


\rm\displaystyle (x - 4) ^(2) + {(y + 4)}^(2) = 36

Explanation:

the given points are the diameter points of circle because notice that in the both points y coordinate is the same therefore it's a horizontal diameter

since (10,-4),(-2,-4) are the diameter points of the circle the midpoint of the diameter will be the centre of the circle

remember midpoint formula,


\displaystyle M = \left( (x _(1) + x_(2) )/(2) , ( y_(2) + y_(2))/(2) \right)

let,


  • \displaystyle x _(1) = 10

  • \displaystyle x _(2) = - 2

  • \displaystyle y _(1) = - 4

  • \displaystyle y _(2) = -4

thus substitute:


\rm\displaystyle M = \left( (10 + ( - 2))/(2) , ( - 4 + ( - 4))/(2) \right)

simplify addition:


\rm\displaystyle M = \left( (8)/(2) , ( - 8)/(2) \right)

simplify division:


\rm\displaystyle M = \left( 4, - 4 \right)

so the centre of the circle is (4,-4)

since it's a horizontal diameter the the redious will be the difference between the x coordinate of the Midpoint and the any x coordinate of the given two points but I'll use (-2,-4) therefore the redious is


\displaystyle r = 4 - ( - 2)

simplify which yields:


\displaystyle\boxed{ r =6}

recall the equation of circle


\displaystyle (x - h) ^(2) + {(y - k)}^(2) = {r}^(2)

we acquire that,

  • h=4
  • k=-4
  • r=6

therefore substitute:


\rm\displaystyle (x - 4) ^(2) + {(y - ( - 4))}^(2) = {6}^(2)

simplify:


\rm\displaystyle (x - 4) ^(2) + {(y + 4)}^(2) = 36

and we are done!

also refer the attachment

(the graph is web resource of desmos)

Find the equation of a circle with a point at ( 10 , - 4 ) and a point at ( -2 , - 4 )​-example-1
User Glosrob
by
5.3k points
3 votes

Answer:

Solution given:

letA=(10,-4)

B=(-2,-4)

centre[C](h,k)=
(10-2)/(2),(-4-4)/(2)=(+4,-4)

radius=
√((4-10)²+(-4+4)²)=6units

we have

Equation of a circle is;

(x-h)²+(y-k)²=r²

(x-4)²+(y+4)²=36

or.

x²-8x+16+y²+8y+16=36

x²-8x+8y+y²=36-32

x²-8x+8y+y²=4

The equation is (x-4)²+(y+4)²=36 or x²-8x+8y+y²=4.

User JJ Pell
by
5.7k points